THE EFFECT OF THE ADDITION OF BROCCOLI (Brassica olaracea l.var italic) ON THE QUALITY OF FISH CARP (Laptobarbus hoevenii) MEATBALLS - Gonal, Hendri; Buchari, Dewita; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research aimed to determine the influence of the addition of broccoliflour on the quality of fish carp meatballs. The methods used in this study wasexperimental, namely conducting a series of experiments on producing carp fishmeatballs added with broccoli flour as a source of fiber and composed as thecompletely randomized design (CRD). The addition of broccoli flour wasconsisted of four treatment levels, those were B0 (0 g), B1 (20g), B2 (40 g) and B3(60 g), which the weight was calculated from the percentage of fish meat weight.The treatments were repeated three times. The quality of fish meatball wasevaluated for the organoleptic value (consistence, texture, aroma, taste) andchemical composition (water, fat, protein, fiber). The results showed that theaddition of the broccoli in the processing of meatballs carp fish indicated asignificant effect on the consistence, taste and texture, but not to the aroma. Theaddition of broccoli flour also affected to the content of water, protein, fat andfiber. The best treatment was the addition of powder 20 g broccoli for the highestquality of fish meatball. The product was showing neat, clean white greenish, byit’s distinctive aroma of meatballs with the fresh carp fish and the aroma of spiceswas not strong, good taste and juicy, and the texture was chewy and solid. Thechemical composition was showing the content of water 67,52%, protein 16,08%,fat 2,48% and fiber 1,82%.Key words: addition, broccoli flour, carp fish, meatballs